Aggregation rate as a function of soil organic matter in heavy clayey Ferralsols - Melo,Thadeu Rodrigues de (2022)
ABSTRACT Heavy clayey Ferralsols are known for their high capacity to form water-stable macroaggregates. However, little is known about how different size classes of macroaggregates exchange mass with increasing organic matter content. This study aimed to characterize and detail aggregation dynamics with increasing organic matter content in these soils. Profiles of three heavy clayey Ferralsols were sampled to isolate the role of organic matter on the stability of aggregates. In this sampling scenario, a conceptual model was established to calculate the aggregation rate of different size classes of water-stable aggregates. This approach allowed the establishment of a critical value for classifying microaggregates in the studied soils (≤0.50 mm) based on their behavior as “building blocks” for macroaggregates when organic matter content is increased. In surface soil layers, where organic matter is higher, most dynamics are expected to happen between macroaggregates classes because free microaggregates are scarce. Consequently, it is important to subdivide macroaggregates into different size classes when evaluating their stability. Quantifying macroaggregates as a single class (e.g., >0.25 or >0.50 mm) was insufficient in representing the macroaggregation dynamics in heavy clayey Ferralsols.